Interpretation of Jihad in the Qur`an - M. Yusuf Yahya (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2015)
There are a lot of meanings given by the experts about jihad. In board outline,jihad means the war against the enemies, the exertion of every capability andevery power as well as the upholding of the truth. In the contemporary context,jihad means an intensive effort of one or a group for the public purpose that couldimprove a certain realm in a certain region, such as the elimination of terrorismand the abolition of poverty in Indonesia. The context of jihad in the Qur`anverses even one verse does not point deliberately to the war with the exception ofa country is colonized or it is under attack. It neither points to the violence nor theterrorism. The research of this article is intended to strengthen the meaning ofjihad due to various sorts of terrorism that happen in Indonesia, as a result of theinquiry and the case trial in court conducted to the perpetrators, they areoccasionally influenced with jihad doctrine and revenge versus forgiveness. Inanother part, the psychological indications such as frustration, disappointment,injustice, anger versus empathy are the factors that lead to their violent acts too.Unfortunately, the terrorism is propagated in various regions that are made asthe basic training camps. The research of this article depicts the meaning of Jihadbased on the Qur`an. The data for completing this work is based on the classicmanuscripts and the contemporary viewpoints. The research of this work is alsointended to stress on the denial of terrorism in the Qur`an. In academic value, theresearch of this work is expected to be useful to develop the contemporaryperspectives of jihad.